THE SPECIFIC ORDINATION AND CLUSTERING OF MANGROVE ECOSYSTEM IN SEGARA ANAKAN - Hilmi, Endang; Junaidi, Teuku; Mahdiana, Arif; Prayogo, Norman Arie; Dewi, Rose; Rahayu, Sri (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Mangrove ecosystem has specific ordination and clustering following the adaptation toward the environment properties and species competition. This research aimed to develop a specific ordination to support ecosystem stability. The research was carried out with a multidimensional system using density and environmental properties with similarity and Euclidian distance indexes. The results showed that West Segara Anakan had 6 ordination areas, and East Segara Anakan had 5 ordinations with the range density of 68-3373 trees/ha and 550-2975 trees/ha. Based on environmental properties, WSAL had nitrate, phosphate, pyrite, water and soil pH, and water salinity levels of 10.57-31.44 mg/lt, 8.44-22.89 mg/lt, 1.03-1.57 %, 5.60-7.78, 6.58-7.03, and 24.15-33.85 ppt, respectively. In ESAL, nitrate, phosphate, pyrite, water and soil pH, and water salinity were within the range of 19.72-28.98 mg/lt, 10.83-19.72 mg/lt, 1.28-2.91%, 6.35-7.05, 5.91-6.23, and 18.00-32.33 ppt. Furthermore, specific ordination showed that Avicennia marina, Rhizophora stylosa, Rhizophora apiculata, and Nypa frutican had the highest level of adaptation. I special thanks for research Terapan Unsoed 2023 to support this research.